Effect of photobiomodulation as preventive treatment of diabetic foot ulcer: randomised, controlled, double-blind, clinical trial protocol - Lara Jansiski Motta; Anna Carolina Ratto Tempestini Horliana; Kristianne Porta Santos Fernandes; Raquel Agnelli Mesquita-Ferrari; Sandra Kalil Bussadori; Roselene Lourenço; Silvana Torres Perez; Cinthya Cosme Gutierrez Duran; Alexandre Rocha Santos Padilha; Tainá Caroline dos Santos Malavazzi (BMJ Open)
Introduction The prevention of diabetic foot ulcer (DFU) involves the classification of risk, systemic care, regular examinations, foot care, therapeutic education and adjunct treatments. Photobiomodulation (PBM) has been successfully administered for the healing of DFU and its preventive effects have drawn the interest of researchers.Methods and analysis The purpose of the study is to assess the effect of PBM for the prevention of DFU through a randomised, controlled, double-blind, clinical trial. Individuals from 18 to 75 years of age of both sexes with type 2 diabetes mellitus (DM) at moderate to high risk of developing DFU will be randomly allocated to two groups of 32 participants each. The PBM group will wear a boot with 1344 light-emitting diodes (LEDs)—504 with a wavelength of 660 nm located on the sides of the boot (28.5 mW, 10 J per LED), 504 with a wavelength of 850 nm also on the sides of the boot (23 mW, 8 J per LED), 168 with a wavelength of 660 nm on the base of the boot (28.5 mW, 10 J per LED) and 168 with a wavelength of 850 nm also on the base of the boot (23 mW, 8 J per LED). The boot will be worn once a day for 6 min over 60 days and the participants will also receive therapeutic education. The control group will wear a non-therapeutic LED boot (sham) under the same conditions and will also receive therapeutic education. Assessments will be performed at the beginning of the study, after 30 days (clinical examination) and after 60 days (clinical examination, assessment of peripheral neuropathy (PN) and peripheral artery disease (PAD), blood and urine examinations and quality of life).Ethics and dissemination This protocol received approval from the Human Research Ethics Committee of Nove de Julho University and the Mandaqui Hospital Complex (certificate number: 66098522.0.3001.5511; final approval date: 22 June 2023). The findings will be published in a peer-reviewed journal.Trial registration number NCT06353568, ClinicalTrials.gov.